Data management based on blockchain and edge computing for Internet of things - Guanjie CHENG; Zhengjie HUANG; Shuiguang DENG (物联网学报)
The popularity of smart devices has driven the development of the application of Internet of things (IoT) technology,and the resulting massive amount of IoT data has brought challenges to traditional centralized data management methods,such as performance,privacy,and security.Therefore,a data management framework of IoT based on blockchain and edge computing was proposed to support the distributed IoT data management.The distributed storage and access control could be provided by the framework for the IoT data.At the same time,a set of the built-in encryption scheme was designed to protect the data security and privacy and safeguard the data ownership.By introducing edge computing,the scalability bottleneck of the blockchain the system was relieved.The processes of data storage and data access based on this framework were given,and the algorithm of the system implementation based on the smart contract technology was explained in detail.Experiments show that the IoT data management system based on this framework outperforms the traditional cloud-based data management systems.